Internal audit: corporate governance issues impacting its existence in ASX listed firms and its influence on earnings management - Choudhury Lema, Aklema (Curtin University, 2015)
This study examines the association of corporate governance mechanisms with internal audit function, including outsourcing for top ASX listed firms. The study further explores relationships between internal audit and earnings management. Using agency theory, cross-sectional quantitative analyses are conducted using 240 ASX firms, including survey and financial report data for 2011. Main results indicate that corporate governance mechanisms significantly influence the status of internal audit, however there is no significant association with earnings management.